LINGUISTIC VARIATION AND ITS ASSUMPTIONS: AN APPROACH TO DIATOPIC VARIATION IN A TRISTE PARTIDA DE PATATIVA DO ASSARÉ - Mirele Alves Medeiros, Maria; Willames Cirino Oliveira, Wesley (Revista Gênero e Interdisciplinaridade, 2024)
This work deals with the study of linguistic variations, having as its core the differences found in social interaction in people’s daily lives. It was constructed considering the difficulty some teachers have in dealing with the heterogeneity of verbal expressions used in communities. It does not aim to judge any conception, especially the standard norm, but to provide a new perspective in a judicious manner, taking into account the relationship with the events of these variations, observing factors such as: geographic space, the degree of formality required for each situation experienced, culture, the individual being and the community in which he or she is inserted. This is what is set out in the chapters that, when dealing with linguistic variation, bring in their core the historical and conceptual marks, in the light of various theorists, discussing the sociolinguistic phenomenon, as well as reflecting on the possibility of a variationist analysis, focusing on diatopic variation, orality and regionalisms in the light of popular culture. The research also provides an opportunity for a reflective approach, focusing on the analysis of the diatopic variation present in the poem “A triste partiu de Patativa do Assaré”.